O processo de implementação da gestão por competências na Universidade Federal de Santa Maria (UFSM): análises e diretrizes - Bassan, Filipe Venturini (2019)
The present study aimed to analyze the construction of processes for the implementation of competency management (GC) at Federal University of Santa Maria (UFSM). The theoretical reference included three main topics: Management of People in Public Administration; Competency Management; and Competency Management in Public Administration, emphasizing the model of Brandão and Bahry (2005) considered the most appropriate to guide this research. As for the method, the study was characterized as an exploratory-descriptive, applied, with qualitative approach and deductive logic, held at the UFSM. Data were collected through 22 semi-structured individual interviews (with the Pro-Rector of People Management, competency management commission, and Directors of Teaching Units), as well as documentary analysis and non-participant observation. For the analysis of the data, was used the technique of Content Analysis. The main results show that the UFSM has defined and is carrying out three main steps for the implementation of the GC: awareness raising, identification of organizational competencies and mapping of individual competencies. As for the reasons that led the Institution to introduce this model, the following stand out: the need to leave the people management (GP) area more modern and strategic; comply with legal demand; comply with the recommendations of control bodies; to support people management processes; and to respond to the criticisms about servers that assumed managerial positions without having the necessary competences for such. The main challenges and difficulties that the commission of GC is facing in the conduct of the project are: lack of exclusive dedication to activities; lack of space and furniture for meetings; the fact that it is a new and complex model in the public service, with few practices; awareness of the whole institution; reduced staff; large workload; resistance of servers; and doubt about the support of managers. Despite this, the interviewees believe that the implementation of GC in the University is feasible. Furthermore, the results revealed that most of the Directors of Teaching Units of the UFSM are not sufficiently prepared to receive the GC. Also, the Directors presented bottlenecks and suggestions of changes in the University aiming at the success of the model, among them: review the administrative structure and the distribution of servers; make it clear what is expected of each function; change the organizational culture; to sensitize the entire university community; invest in the creation and use of technological tools; make decisions less political and more technical; decentralize planning of institutional actions; reduce bureaucracy; to have political courage; and to assign training courses as a prerequisite to assume managerial positions. The Directors also pointed out the possible outcomes that the GC will bring to UFSM, if it is implemented, namely: streamlining and standardization of processes; improvement in service to the community; improvement in the motivation and well-being of the servers; improvement in the selection, preparation and training of managers; economic improvement for the University; and assistance in qualification of the Institution. Finally, guidelines were proposed for the GC to be implemented in the best possible way in the UFSM. It was also noticed that the GC is still embryonic in most Brazilian federal universities, mainly due to the lack of methodologies and clear legislations that provide legal certainty, especially to the GP area, regarding the application of the practices of this model.